Bending but Not Breaking?: Foreign Investor Pressure and Dividend Payouts by Japanese Firms. Issue 3 (28th April 2016) - Jung, Jiwook; Mun, Eunmi
Abstract: This article examines the global diffusion of shareholder‐oriented governance practices, using the case of dividend payouts by Japanese firms. While Japanese firms previously retained profits for rainy days or new ventures, their dividend payouts began to increase in the 1990s, rapidly catching up with the levels prevailing in the United States. Following prior research, we focus on the role of foreign investors in this process but provide a more nuanced account of their influence, using panel data on 2, 036 publicly traded Japanese firms from 1990 to 2005. First, we show that pressure from foreign investors increased dividends by Japanese firms not only directly but also indirectly, by extending the cognitive boundaries of organizational fields of Japanese firms beyond their local peers and toward their global competitors. Second, we show that although Japanese firms that remained deeply embedded in the traditional, stakeholder‐oriented governance system resisted shareholder‐oriented governance practices, even such firms yielded under pressure from both foreign and domestic investors. We conclude with theoretical implications of our findings for the literature on the global diffusion of shareholder value and its broader political and social consequences.